The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3748/wjg.v22.i7.2294
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tim-3 in hepatitis B virus infection: An overview

Abstract: Hepatitis B virus (HBV) infection has received increasing public attention. hBV is the prototypical member of hepadnaviruses, which naturally infect only humans and great apes and induce the acute and persistent chronic infection of hepatocytes. A large body of evidence has demonstrated that dysfunction of the host anti-viral immune response is responsible for persistent HBV replication, unresolved inflammation and disease progression. Many regulatory factors are involved in immune dysfunction. Among these, T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 77 publications
1
37
0
1
Order By: Relevance
“…Increased evidence demonstrated the dynamic expression and diverse functions of Tim-3 in different disease models, especially in liver diseases including viral hepatitis, acute alcohol hepatitis, and HCC. 17,32,33 Our present study demonstrated that Tim-3 expression in fatty livers of NASH mice was significantly increased and acted as a modulator in the process of NASH (Fig. 1).…”
Section: Discussionsupporting
confidence: 59%
“…Increased evidence demonstrated the dynamic expression and diverse functions of Tim-3 in different disease models, especially in liver diseases including viral hepatitis, acute alcohol hepatitis, and HCC. 17,32,33 Our present study demonstrated that Tim-3 expression in fatty livers of NASH mice was significantly increased and acted as a modulator in the process of NASH (Fig. 1).…”
Section: Discussionsupporting
confidence: 59%
“…[1522] Importantly, the expressions of PD-1 and TIM-3 in liver tissues of chronic HBV infection and HBV-related HCC are related to the severity of liver inflammation and T cell exhaustion and the prognosis of HCC patients. [17,19,21,2326] The polymorphisms of PD1 and TIM3 are associated with the development of HBV-associated liver diseases and the prognosis of patients with HBV-related HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study and other report demonstrated that expression of Tim‐3 was significantly upregulated on monocytes in CHB patients and may play important roles in the pathogenesis of CHB. However, the role of Tim‐3 signalling on function of monocyte in CHB patients has not been well understood …”
Section: Discussionmentioning
confidence: 99%